ANALISA KORELASI ANTARA FREKUENSI DENGAN BENTANG JEMBATAN BERDASARKAN UJI DINAMIK - Hinawan T. Santoso; Laely F. Hidayatiningrum; Adityo B. Utomo; Juandra Hartono; Masrianto - (Jurnal Jalan-Jembatan, 2021)
The population of bridges on National Road in 2020 has reached 21,054 units with a total length of 587,309 meters. About 10.5% of bridges have a service life of less than 10 years, 68.1% in the range of 10 - 50 years, and 5.3% more than 50 years. As the service life increases, the condition of the bridge will decrease. This bridge condition is obtained from the results of a detailed inspection using the visual method. The accuracy of this method is highly dependent on the objectivity, ability, and experience of the bridge inspector. The large population of bridges, variations in service life and conditions, and limited experienced inspectors are obstacles in conventional bridge inspections. As an alternative, the dynamic test method can be used to check bridge conditions more quickly and accurately. The natural frequency of the dynamic test can be used to determine the integrity condition and the level of structural damage, by comparing it to the theoretical frequency. So far, the theoretical frequency is determined based on calculations or structural modeling. The limited data of technical specifications, design drawings, and as-built drawings are often an obstacle. Experience and special skills are also needed in calculating or modeling this structure. This study aims to analyze the correlation between frequency and bridge span based on bridge dynamic test data in Indonesia. The results obtained a mathematical formula, where the value of the frequency of the bridge is correlated to the span of the bridge with a correlation coefficient of -0.85. This coefficient shows that the relationship between the variables under consideration is very strong and inverse, where the longer the bridge span, the smaller the vertical frequency value of the bridge. Keywords: Dynamic Test, Bridge Span, Vertical Frequency, Correlation Analysis, Mathematical Formula